FIFA, the video game: a major vehicle for soccer`s popularization in the United States - Markovits, A. S.; Green, A. I. (Sport in Society: Cultures, Commerce, Media, Politics, 2017)
Soccer in the United States is undergoing major changes. The game`s growth on the fields of the country`s suburbs and among its middle class has been nothing short of sensational. Major events such as the World Cup - both Men`s and Women`s - have gained the sport millions of followers. In addition, a growing number of Americans has come to incorporate Europe`s most prestigious tournaments and prominent leagues into its daily sports consumption. Our study analyses how a particular venue - EA Sports` FIFA video game series - has contributed to this fascinating ongoing development. While at this temporal stage, soccer`s popularity in following (in notable contrast to playing) continues to lag behind that of America`s `Big Four` of football, baseball, hockey and basketball, recent events, aided by the burgeoning proliferation of FIFA the video game, may catapult soccer`s cultural presence into the Big Four`s in coming years.